Cxcl12 Deletion in Mesenchymal Cells Increases Bone Turnover and Attenuates the Loss of Cortical Bone Caused by Estrogen Deficiency in Mice. (25th March 2020) - Ponte, Filipa; Kim, Ha‐Neui; Iyer, Srividhya; Han, Li; Almeida, Maria; Manolagas, Stavros C
ABSTRACT: CXCL12 is abundantly expressed in reticular cells associated with the perivascular niches of the bone marrow (BM) and is indispensable for B lymphopoiesis. Cxcl12 promotes osteoclastogenesis and has been implicated in pathologic bone resorption. We had shown earlier that estrogen receptor α deletion in osteoprogenitors and estrogen deficiency in mice increase Cxcl12 mRNA and protein levels in the BM plasma, respectively. We have now generated female and male mice with conditional deletion of a Cxcl12 allele in Prrx1 targeted cells ( Cxcl12 ∆Prrx1 ) and show herein that they have a 90% decrease in B lymphocytes but increased erythrocytes and adipocytes in the marrow. Ovariectomy increased the expression of Cxcl12 and B‐cell number in the Cxcl12 f/f control mice, but these effects were abrogated in the Cxcl12 ∆Prrx1 mice. Cortical bone mass was not affected in Cxcl12 ∆Prrx1 mice. Albeit, the cortical bone loss caused by ovariectomy was greatly attenuated. Most unexpectedly, the rate of bone turnover in sex steroid–sufficient female or male Cxcl12 ∆Prrx1 mice was dramatically increased, as evidenced by a more than twofold increase in several osteoblast‐ and osteoclast‐specific mRNAs, as well as increased mineral apposition and bone formation rate and increased osteoclast number in the endosteal surface. The magnitude of the Cxcl12 ∆Prrx1 ‐induced changes were much greater than those caused by ovariectomy or orchidectomy in the Cxcl12 f/f mice. These results strengthen the evidence that CXCL12 contributes to the loss of cortical bone mass caused by estrogen deficiency. Moreover, they reveal for the first time that in addition to its effects on hematopoiesis, CXCL12 restrains bone turnover—without changing the balance between resorption and formation—by suppressing osteoblastogenesis and the osteoclastogenesis support provided by cells of the osteoblast lineage. © 2020 American Society for Bone and Mineral Research.